Phase diagram of the quaternary system LiCl+MgCl2+KCl+H2O at 323.15 K. (June 2017) - Yang, Haitang; Liang, Tengyu; Zeng, Dewen; Yue, Jianling; Du, Yong
ABSTRAT: Solubility isotherms as well as the corresponding solid phases of the quaternary system LiCl+MgCl2 +KCl+H2 O and the eutectic points for the ternary systems LiCl+MgCl2 +H2 O, LiCl+KCl+H2 O and MgCl2 +KCl+H2 O at 323.15 K have been elaborately determined by an isothermal equilibrium method. Five crystallization fields including two double salts (LiCl·MgCl2 ·7H2 O(s) and KCl·MgCl2 ·6H2 O(s)), two hydrate salts (MgCl2 ·6H2 O(s) and LiCl·H2 O(s)) and one single salt (KCl(s)) were detected in the quaternary system. The reliability of the experimental results were verified both by testing the phase diagram rule and comparing with the literature data. It was found that all of the results were accordance with the phase diagram rule, and moreover, the excellent agreement between the experimental data and the literature data was also obtained, which indicate that the solubility data obtained in this work are reliable. Based on the quaternary phase diagram, the example was provided for industrial application. The measured phase diagram reported in this work are the essential tool to guide industrial process of extracting Li from the salt lake brine containing MgCl2 and LiCl using KCl reagent.